Risk factors for COVID-19 pneumonia in patients with hematological malignancies: a multi-center, prospective study in China - Li, Jun; Chen, Ran; Cao, Lin; Liu, Yi; Zhang, Yong; Wei, Xia; Liu, Zhanshu; Yang, Zailiang; Liu, Ling; Zhou, Meiyu; Xu, Guofa; Chen, Lanting; et al. (Frontiers in Immunology, 2024)
PurposeWe aimed to investigate risk factors for COVID-19 pneumonia in patients with hematological malignancies (HM) after Omicron infection.MethodsData from a registered multi-center, prospective, observational study (ChiCTR2300071830) during the latest Omicron BA.5.2 wave in Chongqing, China was used for analysis.ResultsA total of 475 HM patients enrolled in this study. COVID-19 pneumonia was observed in 15.8% (75/475) of patients, with a median age of 58 years (interquartile range [IQR], 48-69 years) and males accounting for 61.3%. Risk factors associated with COVID-19 pneumonia included: 1) Active disease status of HM at infection, with an odds ratio (OR) of 3.42 (95% confidence interval [CI]: 1.59-7.37, P=0.002) compared to complete remission (CR); 2) Incomplete COVID-19 vaccination, 1-2 doses of the vaccine (OR=2.55, 95% CI: 1.28-5.10, P=0.008) or no vaccination (OR=4.81, 95% CI: 2.45-9.43, P<0.001), as opposed to 3 doses (booster); 3) chemotherapy prior to infection, <6 months (OR=2.58, 95% CI: 1.12-5.96, P=0.027) or ≥ 6 months (OR=2.93, 95% CI: 1.31-6.53, P=0.009) compared to no chemotherapy history; 4) NK-cell reduction (< 150/μL) (OR=2.19, 95% CI: 1.27-3.79, P=0.005) versus a normal range of NK cells. During the 6-week follow-up period, 12 patients (2.5%) died, accounting for 16% of COVID-19 pneumonia patients.ConclusionsOur study investigated risk factors for COVID-19 pneumonia in HM patients after Omicron BA.5.2 infection. Highlights that HM patients with these risk factors may be susceptible to lung involvement after Omicron BA.5.2 infection and need to be taken seriously in clinical practice.Clinical Trial Registrationhttps://www.chictr.org.cn/bin/project/edit?pid=195998, identifier ChiCTR2300071830.